Five-element music therapy nursing interventions for relieving anxiety and pain in a patient undergoing arteriovenous fistula surgery (五行音乐改善1例动静脉瘘手术患者焦虑及疼痛的护理体会) - ZHANG Shaojuan (张少娟); ZHAO Chunhua (赵春华) (中西医结合护理)
This paper summarized the treatment effect and nursing cooperation of using five-element music therapy to relieve the anxiety and pain of a patient undergoing arteriovenous fistula surgery. Key issues of nursing included preoperative nursing, intraoperative coordination, operation methods and music selection of five-element music therapy, postoperative observation and guidance, etc. The intervention of five-element music effectively alleviated the anxiety and depression of the patient, reduced the pain symptom of the patient, promoted the stability of intraoperative blood pressure and heart rate, improved the patients compliacne with surgery, and played a positive role in reducing complications, accelerating postoperative rehabilitation and improving the quality of life. (本文总结1例运用五行音乐改善动静脉瘘手术患者焦虑及疼痛的护理经验, 包括术前护理、术中配合、五行音乐治疗的操作方法及选曲、术后观察及指导等。五行音乐疗法能有效缓解动静脉瘘手术患者焦虑、抑郁状态, 减轻疼痛, 促进术中血压、心率平稳, 提高患者手术配合度。)